2021
DOI: 10.1111/eva.13182
|View full text |Cite
|
Sign up to set email alerts
|

Host evolutionary relationships explain tree mortality caused by a generalist pest–pathogen complex

Abstract: Accidental introductions of plant pests (e.g., fungi, bacteria, viruses, animals, plants) into areas outside their place of origin have resulted in novel species interactions that pose ecological and economic threats to agricultural, urban and wildland landscapes (Donatelli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 102 publications
0
14
0
Order By: Relevance
“…This discordance between host tree phylogeny and susceptibility to the PSHB, as shown in Figures 1, 2, indicates that the trait correlation of susceptibility of different tree species to the PSHB are the results of convergent evolution and not of a common descent. However, Lynch et al (2020) recently demonstrated a strong phylogenetic signal in the relative effects of PSHB and KSHB and their associated fungal symbionts on tree host species in California and South Africa, demonstrating that the severity of multi-host pest impacts in plants can be predicted by host evolutionary relationships. Patterns in the signal indicate that there are several ways to be susceptible, but susceptibility clusters within phylogenetic groups and this clumping becomes more restricted with more impactful interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This discordance between host tree phylogeny and susceptibility to the PSHB, as shown in Figures 1, 2, indicates that the trait correlation of susceptibility of different tree species to the PSHB are the results of convergent evolution and not of a common descent. However, Lynch et al (2020) recently demonstrated a strong phylogenetic signal in the relative effects of PSHB and KSHB and their associated fungal symbionts on tree host species in California and South Africa, demonstrating that the severity of multi-host pest impacts in plants can be predicted by host evolutionary relationships. Patterns in the signal indicate that there are several ways to be susceptible, but susceptibility clusters within phylogenetic groups and this clumping becomes more restricted with more impactful interactions.…”
Section: Discussionmentioning
confidence: 99%
“…While pest attributes are probably important in aligning pests along the specialism-generalism spectrum, for example, viruses are frequently among those with the narrowest host range [16], most pests tend to demonstrate strong phylogenetic conservatism in the hosts they use (e.g. [12,17,18]).…”
Section: Phylogenetic Conservatism In Pest-host Associationsmentioning
confidence: 99%
“…While there is relatively strong evidence that many pest host ranges are phylogenetically circumscribed (e.g. [12,17,44]), it is less well-established whether the impacts pests have on hosts are similarly structured. Many plant traits involved in pest defence, susceptibility, or apparency (e.g.…”
Section: Phylogenetic Constraints On Pest Impactsmentioning
confidence: 99%
“…PSHB is known to have a particularly broad host range, in which both the fungus and beetle are able to establish. [36][37][38] This increases the chances of a suitable host being encountered, thus increasing the chances of successful establishment. To obtain the PSHB host range for South Africa, observations made by researchers during field investigations and reports made by the public to the Forestry and Agricultural Biotechnology Institute, University of Pretoria, and Stellenbosch University were collated.…”
Section: Host Rangementioning
confidence: 99%
“…This wide fungal host range ensures availability of suitable hosts near the introduction point. When beetle populations are very high, the insects appear to assess newly encountered hosts almost indiscriminately for fungal establishment 13,38 , explaining the high numbers of non-reproductive hosts. Such 'attacks' may also lead to severe decline in tree health due to Fusarium wilt 13 .…”
Section: Host Rangementioning
confidence: 99%